Makna Simbolik Tradisi Pemberian Gelar Jajuluk Upacara Pernikahan Masyarakat Komering Sumatera Selatan - Sanjaya, Kiki; Rahma Santhi Zinaida (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the symbolic meaning of the tradition of giving the jajuluk title at the wedding ceremony of the Komering people of South Sumatra. The theory used in this research is Symbolic Interaction Theory. The research method used was a descriptive qualitative approach, then the research object was in the Kertapati Palembang area. Meanwhile, the research subjects were the East Ogan Komering Ulu Education and Culture Service, Ogan Komering Ulu Community Leaders and the Kertapati Palembang Community. The results of this research are that in the Komering tribe there are traditional titles given to the bride and groom at the Komering community's wedding ceremony in Kertapati Palembang. The traditional title referred to in this context is a symbol of respect for someone who has reached adulthood, which is marked by marriage. A person's adult size is determined when they are married. Therefore, for every man at the wedding ceremony he must be given a traditional title, as well as his bride too. The tradition of giving traditional titles has social implications in society in the form of the meaning of these traditional titles in everyday life.